Financial literacy in Japan: Determinants and impacts - Naoyuki Yoshino; Peter J. Morgan; Long Q. Trinh (Asian Development Bank Institute (ADBI), 2017)
Financial literacy is gaining increasing importance as a policy objective in many countries. However, internationally comparable information on financial literacy is still scarce. Recently, the Bank of Japan conducted a major survey of financial literacy and financial behavior covering 25,000 individuals aged from 18 to 79. Our paper used this database to analyze the determinants of financial literacy and the effects of financial literacy on other behaviors. Generally, our study corroborated the findings of studies on other countries, but it uncovered some differences as well. We found that the main determinants of financial literacy are the educational level, income, age, and occupational status and that both financial literacy and general education levels are related positively and significantly to savings behavior and financial inclusion.
Keywords: D14; G11; J26; 330; financial literacy; financial behavior; financial inclusion; household saving; Japan